Search for new dimensions of the educational space: digital and non-digital vectors of development - T. Yu. Krotenko (Цифровая социология)
Sociocultural, ecological, economic circumstances in which the constantly changing world finds itself persistently demand the emergence of new directions and subjects of research in the educational sphere.   The purpose of the article is to identify promising vectors for studying the space of lifelong education.   The following research methods were used: a) analysis of a combination of terms that combine philosophical, socio-cultural, economic and educational meanings; b) analysis of the author’s pedagogical experience in the formats of formal, non-formal and spontaneous education; c) an expert survey conducted online in October 2021; d) content analysis of detailed answers to the questions offered to respondents. As a result, the article outlines previously not obvious sources for creating an interdisciplinary methodological basis, the appearance of which can be predicted at the junctions of various fields of knowledge, in practice-oriented research attempts to implement the ideas of transdisciplinarity. The author’s research diagnoses fundamentally new methodological impulses that exist in science and modern philosophy when considering continuous knowledge as a vital attribute of a modern person. The possibilities that are hidden in paradoxical, at first glance, combinations and at the intersections of previously completely independent knowledge spheres are discussed. This is important for solving the problem of preserving anthropic qualities, which is especially prominent in the course of the chaotic development of learning systems that integrate human nature and artificial intelligence.   The scientific novelty of the work is made up of conclusions about research methods that are most suitable for the formation of new psychological and pedagogical knowledge about permanent education.